Fibrin glue injection method for complex fistula after laparoscopic distal pancreatectomy: a case report - Hideki Izumi; Hisamichi Yoshii; Rin Abe; Masaya Mukai; Eiji Nomura; Hiroyasu Makuuchi (Journal of Medical Case Reports, 2022)
Abstract Background Pancreatic fistula is the most problematic complication in pancreatectomy. Although drainage can be used to relieve this complication, pancreatic surgeons often encounter refractory pancreatic fistula. Fibrin glue injection, with the use of a twofold diluted solution B and a double-lumen tube, was found effective in treating this complicated pancreatic fistula. Case presentation We report the case of a 64-year-old Japanese man who underwent laparoscopic distal pancreatectomy for pancreatic tail cancer. After initial drainage of the pancreatic fistula diagnosed 4 days postoperatively, on day 134, refractory pancreatic fistula was observed using contrast-enhanced computed tomography. We used fibrin glue injection, with a twofold diluted solution containing thrombin and calcium chloride and a double-lumen tube, for treating the refractory fistula; the fluid drainage was almost stopped with no fever or abdominal pain. No recurrence of pancreatic cancer has been observed since the procedure. Conclusions Fibrin glue injection was effective for complicated pancreatic fistula after distal pancreatectomy. Using a twofold diluted solution B containing thrombin and calcium chloride and a double-lumen tube makes possible the thorough injection of fibrin glue.